2022
DOI: 10.2147/ijnrd.s326427
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Impact, and Management Strategies of Anti-Glomerular Basement Membrane Disease

Abstract: Anti-glomerular basement membrane (anti-GBM) disease is a rare but serious autoimmune disease, which is characterized by the development of pathogenic antibodies to type IV collagen antigens in the glomerular and alveolar basement membranes. This results in rapidly progressive glomerulonephritis (GN), alveolar hemorrhage, or both. A variety of environmental factors can trigger the disease in genetically predisposed patients. Temporal associations with influenza, SARS-CoV-2 infection, and COVID-19 vaccination h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…It is particularly important to recognize vaccine-associated GN as a clinical entity, and have awareness of management strategies due to emergence of case reports and series following the implementation of COVID-19 vaccination programs [ 3 , 6 , 8 , 36 , 37 , 38 ]. Recent systematic reviews of renal disease associated with COVID-19 vaccination showed that MCD occurred most frequently, followed by IgA nephropathy, and vasculitis [ 5 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly important to recognize vaccine-associated GN as a clinical entity, and have awareness of management strategies due to emergence of case reports and series following the implementation of COVID-19 vaccination programs [ 3 , 6 , 8 , 36 , 37 , 38 ]. Recent systematic reviews of renal disease associated with COVID-19 vaccination showed that MCD occurred most frequently, followed by IgA nephropathy, and vasculitis [ 5 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Epidemiological studies have noted a bimodal age distribution, characteristically affecting males in their third decade of life with renal and pulmonary involvement, and a second peak among females in their sixth to seventh decade of life with isolated renal disease. 1,4 Most patients present with features of rapidly progressive glomerulonephritis, and a subset of patients may also develop diffuse alveolar hemorrhage. 5 The standard therapeutic regimen for anti-GBM disease involves therapeutic plasma exchange (TPE), cyclophosphamide, and corticosteroids to rapidly remove and inhibit autoantibody production and reduce organ inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…As it is characterized by circulating autoantibodies targeting basement membrane antigens, it is considered an immune‐complex small‐vessel vasculitis 1‐3 . Epidemiological studies have noted a bimodal age distribution, characteristically affecting males in their third decade of life with renal and pulmonary involvement, and a second peak among females in their sixth to seventh decade of life with isolated renal disease 1,4 . Most patients present with features of rapidly progressive glomerulonephritis, and a subset of patients may also develop diffuse alveolar hemorrhage 5 …”
Section: Introductionmentioning
confidence: 99%
“…Anti-glomerular basement (anti-GBM) disease is a rare autoimmune vasculitis affecting alveolar and GBM membranes, with reported incidence of 0.4-2.8 cases per million, 1 occurring predominantly in male Caucasians, with a bimodal age distribution in the third and seventh decades. 2,3 While 80-90% of patients present with rapidly progressive glomerulonephritis, 40-60% of these cases present with coexisting pulmonary manifestations, 3,4 with isolated pulmonary manifestations seen in less than 10% of cases. 2,5 Here, we report two cases of isolated pulmonary anti-GBM disease presented to a regional hospital in Central Western New South Wales (NSW), Australia.…”
mentioning
confidence: 99%
“…2,3 While 80-90% of patients present with rapidly progressive glomerulonephritis, 40-60% of these cases present with coexisting pulmonary manifestations, 3,4 with isolated pulmonary manifestations seen in less than 10% of cases. 2,5 Here, we report two cases of isolated pulmonary anti-GBM disease presented to a regional hospital in Central Western New South Wales (NSW), Australia.…”
mentioning
confidence: 99%